(untitled) (Journal of Engineering, 2012)
Physical and chemical adsorption analyses were carried out by nitrogen gas using ASTM apparatus at 77 K and hydrogen gas using volumetric apparatus at room temperature respectively. These analyses were used for determination the effect of coke deposition and poisoning metal on surface area, pore size distribution and metal surface area of fresh and spent hydrodesulphurization catalyst Co-Mo2O3 . Samples of catalyst (fresh and spent) used in this study are taken from AL-Dura refinery. The results of physical adsorption shows that surface area of spent catalyst reduced to third compare with fresh catalyst and these catalysts exhibit behavior of type four according to BET classification ,so, the pores of these samples are cylindrical, and the pores of fresh catalyst suffers during the hydrodesulphurization . The result of chemical adsorption shows that the metal surface area of fresh catalyst is 50.72 m2/g while it reduced to 39.04 m2/g for spent catalyst.